2018
DOI: 10.1002/pros.23720
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid WIN 55,212‐2 induces cell cycle arrest and apoptosis, and inhibits proliferation, migration, invasion, and tumor growth in prostate cancer in a cannabinoid‐receptor 2 dependent manner

Abstract: Background Cannabinoids have demonstrated anticarcinogenic properties in a variety of malignancies, including in prostate cancer. In the present study, we explored the anti‐cancer effects of the synthetic cannabinoid WIN 55,212‐2 (WIN) in prostate cancer. Methods Established prostate cancer cells (PC3, DU145, LNCaP) were treated with varying concentrations of WIN. Cell proliferation was determined by the MTS assay. The anti‐migration and anti‐invasive potential of WIN was examined by the wound healing assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…To date, an increasing number of preclinical studies have reported exciting anticancer properties of cannabinoid-related drugs, both in vitro and in xenograft models of several human cancers, including prostate cancer [1][2][3][4][5][6][7][8][9][10][11][12][13]. Interestingly, cannabinoids have been shown to selectively target tumor cells, which upregulate CBs compared with their healthy counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, an increasing number of preclinical studies have reported exciting anticancer properties of cannabinoid-related drugs, both in vitro and in xenograft models of several human cancers, including prostate cancer [1][2][3][4][5][6][7][8][9][10][11][12][13]. Interestingly, cannabinoids have been shown to selectively target tumor cells, which upregulate CBs compared with their healthy counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer patients, high expression of CB 1 has been associated with a worse prognosis [6,7], and several authors reported CB 1 -mediated anti-proliferative and anti-invasive effects of cannabinoids in prostate cancer cells [8][9][10][11][12]. Furthermore, it has been recently demonstrated that CB 2 also controls tumor cells proliferation, migration, and invasion in both prostate cancer cell lines and in vivo models [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the risk of bias [ 49 ] assessment in these studies are presented in Table 1 (individual scores) and Figure 2 . Randomization was only reported in two studies (33.3%) [ 33 , 46 ], but it was unclear whether this occurred in the other studies. Similarly, temperature controls were only reported in two studies (33.3%) [ 33 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…No information was provided regarding attrition bias in these papers. Random group allocation was reported for two studies, but was not clear in the others [ 33 , 46 ]. The blinding of examiners was high in one study, but unclear in the others [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation